Process for improving hydrolysis rate of titanium dioxide by sulfuric acid method
Patent Information
- Application Number
- CN202510860370.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2045-06-25
AI Technical Summary
[0004]经过前期的探索试验发现,单纯的以增加晶种加量来提高水解率具有一定的可行性,但成本也会增加,最主要的是晶种制备槽的体积也不满足需要;另外当水解晶种的碱钛比偏低时可以采用提高碱钛比以提高水解率,但是,当碱钛比达到0.18以后,晶种稳定性下降速度快,与水解钛液预热时间不匹配;而且增加晶种碱钛比和提高晶种加量对水解率提高并不多,效益不明显
[0023]1、采用单独的浓钛液制备晶种,克服了现有高浓度外加水解晶种稳定性因浓度低、F值不高等因素影响无法调控,无法调整水解晶种工艺,改变水解晶种大小和数量,从而无法提高水解率的缺点;通过提高碱液浓度,在保证碱液加量的前提下提高碱钛比,水解晶种制备槽不用增加,相同的晶种钛液加量时水解率可提高约0.64%,亮度白度均有提升,使得晶种成本增加非常少,操作简单,能够稳定低浓度钛液水解质量。
Abstract
Description
Technical Field
[0001] This invention relates to the field of titanium dioxide hydrolysis technology, and more specifically, to a process for improving the hydrolysis rate of sulfuric acid-based titanium dioxide. Background Technology
[0002] Hydrolysis is a crucial step in the production of titanium dioxide using the sulfuric acid process. It directly determines the quality of metatitanic acid and ultimately the quality of the titanium dioxide product. Most manufacturers use an external seed crystal hydrolysis process, which involves reacting alkali with liquid titanium to prepare hydrolyzed seed crystals.
[0003] Currently, the specifications for the hydrolyzed titanium solution in the sulfuric acid process for producing pigment-grade titanium dioxide vary among different companies. Most control the concentration within the range of 185-200 g / L, iron-to-titanium ratio of 0.28-0.38, and F-value of 1.80-1.95. The same titanium solution is used for both the seed crystal hydrolysis and the hydrolyzed titanium solution. However, to achieve higher hydrolysis rates, the F-value of the titanium solution is generally controlled at the lower limit of 1.80-1.90, and the iron-to-titanium ratio at 0.28-0.32. Simultaneously, the titanium solution concentration is generally controlled as low as possible, around 190 g / L, to consider concentration costs. Therefore, the alkali-to-titanium ratio for high-concentration seed crystals cannot be too high; otherwise, the seed crystal stability decays too quickly, and the preheating time of the hydrolyzed titanium solution cannot be matched. Thus, it is generally controlled below 0.18, with a hydrolysis rate limit of 96-96.2%, where there is no further room for improvement. For domestic titanium dioxide producers using the sulfuric acid process with an annual output of 100,000 tons, a 1% increase in hydrolysis rate is equivalent to a 0.9% increase in the overall TiO2 yield, resulting in an annual output increase of 700 tons and a net income increase of 10 million yuan. Since the TiO2 yield in titanium dioxide production significantly impacts cost control and profits, and increasing the hydrolysis rate in the hydrolysis process can significantly improve the overall TiO2 yield, technologies and methods to improve the hydrolysis rate are currently needed in this field.
[0004] Preliminary experiments revealed that simply increasing the amount of seed crystals to improve the hydrolysis rate is feasible, but it also increases costs. Most importantly, the volume of the seed crystal preparation tank is insufficient. Additionally, when the alkali-to-titanium ratio of the hydrolysis seed crystals is low, increasing the alkali-to-titanium ratio can improve the hydrolysis rate. However, when the alkali-to-titanium ratio reaches 0.18, the stability of the seed crystals decreases rapidly, which is not compatible with the preheating time of the titanium hydrolysis solution. Moreover, increasing the alkali-to-titanium ratio and increasing the amount of seed crystals do not significantly improve the hydrolysis rate, and the benefits are not obvious. Summary of the Invention
[0005] The purpose of this invention is to provide a process for improving the hydrolysis rate of titanium dioxide produced by the sulfuric acid process. By using different concentrations of titanium liquid with different seed crystals, different seed-to-alkali ratios are obtained, ultimately optimizing the number of seed crystals to improve the hydrolysis rate.
[0006] This invention is achieved through the following technical solution:
[0007] A process for improving the hydrolysis rate of titanium dioxide produced by the sulfuric acid process includes the following steps:
[0008] Seed crystal preparation: Titanium liquid with a concentration of 160-250 g / L and alkaline solution with a mass concentration of 10-25% are preheated separately. Then, the titanium liquid is dispersed in the alkaline solution with an alkaline-to-titanium ratio of 0.20-0.38. After aging, hydrolyzed seed crystals are obtained.
[0009] Hydrolysis: Preheat the hydrolyzed titanium solution with a concentration of 160-190 g / L, add 2.5-5% of the TiO2 mass of the hydrolyzed titanium solution as hydrolyzed seed crystals to form a hydrolysis system, heat to boiling, maintain a gentle boil, and when the hydrolyzed titanium solution turns white, add a composite treatment agent for induction. After induction, continue to heat and maintain a gentle boil, then add dilution water and maintain the system at a gentle boil. The hydrolysis is then complete.
[0010] Since the number of hydrolyzed seed crystals is affected by the alkali-to-titanium ratio, appropriately increasing the alkali-to-titanium ratio can increase the number of seed crystals, thereby improving the hydrolysis rate. Currently, increasing the alkali-to-titanium ratio is usually achieved by increasing the amount of alkali solution. However, excessive alkali solution can lead to an excessively high pH value, which may accelerate the hydrolysis reaction, resulting in coarse and unevenly distributed metatitanic acid particles, reducing product uniformity. Excessive OH-... - Excessive alkali solution may cause excessive hydroxylation of the seed crystal surface or the formation of colloidal Ti(OH)4, resulting in reduced seed crystal activity and inability to effectively induce uniform hydrolysis of the subsequent titanium solution; excessive alkali solution may cause some seed crystals to dissolve (generating titanate ions), which will then reprecipitate into irregular particles when the pH fluctuates, thus destroying the uniformity of the seed crystals.
[0011] Based on this, the inventors modified the alkali-to-titanium ratio by increasing the alkali concentration. Hydrolyzed seed crystals were prepared by reacting a high-concentration alkali solution with a high-F-value, high-concentration titanium solution. This process generates a large amount of the hydrolyzed seed crystal precursor—orthotitanic acid—without increasing the amount of alkali, thereby increasing the number of seed crystals. The seed crystals are rich in hydroxyl groups (-OH) on their surface, exhibiting high activity and effectively inducing the directional hydrolysis of the titanium solution. When these hydrolyzed seed crystals are used in the hydrolysis of titanium solution, due to their small particle size and large quantity, a higher hydrolysis rate is achieved under the same seed crystal dosage, reducing seed crystal costs and improving production efficiency.
[0012] Preferably, the F-value of the titanium solution used for seed crystal preparation is 1.95-2.25. Preparing hydrolyzed seed crystals using a high-concentration, high-F-value titanium solution and a high-concentration alkaline solution helps increase the number of seed crystals, ensures the stability of the seed crystal system, and matches the preheating time of the hydrolyzed titanium solution.
[0013] Preferably, during seed crystal preparation, the preheating temperature is 70-95℃, the ripening temperature is 80-102℃, and the ripening time is 5-50min.
[0014] Preferably, during seed crystal preparation, the titanium liquid is dispersed into the alkaline solution within 5-10 minutes, and the dispersion is carried out by stirring at a speed of 300-350 r / min. The alkaline solution is a sodium hydroxide solution.
[0015] Preferably, the F value of the hydrolyzed titanium solution is 1.80-1.95.
[0016] Preferably, the mass ratio of the composite treatment agent to TiO2 in the hydrolyzed titanium solution is 0.5-1.0%.
[0017] Preferably, the composite treatment agent comprises, by weight, 5-15 parts ammonium carbonate, 5-10 parts aluminum sulfate, 5-10 parts potassium sulfate and 10-20 parts polyoxyethylene ether phosphate.
[0018] During the hydrolysis of titanium solution, the dispersibility of the hydrolysis system and the quality of the seed crystals are key factors determining the quality of metatitanic acid, ultimately affecting the quality of the pigment titanium dioxide product. This invention, by adding a composite treatment agent, improves the dispersibility of the material in the hydrolysis system, allowing for more uniform and thorough hydrolysis of the titanium solution induced by the seed crystals. It also enhances the stability of the seed crystals, ensuring their activity and nucleation sites, promoting the uniformity of the hydrolysis reaction, thereby increasing the hydrolysis rate of the titanium solution and improving the washing efficiency of hydrolyzed metatitanic acid.
[0019] Ammonium carbonate, as a weakly basic salt, can slowly release NH4+. 4+ and CO3 2- Ions, CO3 2- With H in the solution + The reaction produces HCO 3- Alternatively, CO2 can be used to stabilize the pH value, preventing hydrolysis side reactions caused by excessive acidity or alkalinity in certain areas, and avoiding drastic fluctuations in the pH value of the titanium solution; NH4+ 4+ It binds to titanium complex anions, reducing their solubility and promoting directional crystallization. In titanium liquid systems, ammonium carbonate neutralizes free acids (such as H+). + Maintain the pH within a suitable range (usually weakly acidic to neutral) to prevent Ti from forming. 4+ Premature hydrolysis of metal ions or formation of oxygen-containing precipitates. Ammonium carbonate's NH4+... 4+It can adsorb onto the seed crystal surface, forming an electric double layer structure, enhancing the electrostatic repulsion between colloidal particles, affecting the surface charge state of the seed crystal, and improving colloidal dispersion and reducing particle aggregation through adsorption or complexation, thereby enhancing the catalytic activity and uniformity of the seed crystal. Aluminum sulfate and potassium sulfate can regulate hydrolysis kinetics, optimize hydrolysis equilibrium, and delay hydrolysis to improve seed crystal activity. Aluminum sulfate can also enhance high-temperature stability and reduce side reactions. The molecular structure of polyoxyethylene ether phosphate contains hydrophilic phosphate groups and hydrophobic polyoxyethylene ether chains, which can inhibit the aggregation of seed crystal particles through electrostatic repulsion and steric hindrance effects, ensuring uniform seed crystal size distribution. Specifically: phosphate groups (-PO4) 3- After ionization, the phosphate groups adsorb onto the surface of the seed crystal particles, forming an electric double layer structure. Coulomb repulsion prevents particles from approaching each other. The hydrophobic polyoxyethylene ether chains extend into the solution, forming a physical barrier that hinders direct contact between particles. This effect is more pronounced in low-concentration titanium solutions, reducing secondary agglomeration during seed crystal growth. The ionization of the phosphate groups imparts a negative charge to the surface of the seed crystal particles, enhancing the stability of the colloidal system. This charge regulation prevents non-uniform nucleation caused by localized supersaturation. The phosphate groups react with titanium ions (Ti... 4+ A weak complexation reaction occurs, slowing down the hydrolysis rate and thus controlling the nucleation and growth balance of the seed crystals, thereby enhancing the seed crystal activity. As a surfactant, polyoxyethylene ether phosphate can reduce the surface tension of the solution, promote the uniform nucleation of titanate colloids, and at the same time, it works synergistically with aluminum sulfate and potassium sulfate to improve the kinetic conditions of the hydrolysis reaction.
[0020] The composite treatment agent overcomes the shortcomings of traditional inorganic salt dispersants, such as easy introduction of impurities, sensitivity to acidity, and easy decomposition, as well as the difficulty of removing impurities from polymeric dispersants, which affect the quality of titanium dioxide. It can simultaneously improve the dispersion performance and stability of hydrolyzed seed crystals to promote the hydrolysis of titanium liquid and increase the hydrolysis rate.
[0021] Preferably, the composite treatment agent is prepared by mixing ammonium carbonate, aluminum sulfate and potassium sulfate and then adding them to polyoxyethylene ether phosphate, followed by ultrasonic treatment for 5-10 minutes.
[0022] The technical solution of the present invention has at least the following advantages and beneficial effects:
[0023] 1. The method of preparing seed crystals using a separate concentrated titanium solution overcomes the shortcomings of existing high-concentration externally added hydrolyzed seed crystals, which cannot be controlled due to factors such as low concentration and low F value, and cannot adjust the hydrolysis seed crystal process, change the size and number of hydrolyzed seed crystals, thus failing to improve the hydrolysis rate. By increasing the concentration of alkali solution and increasing the alkali-to-titanium ratio while ensuring the amount of alkali added, the hydrolysis seed crystal preparation tank does not need to be increased. With the same amount of titanium solution added for the same seed crystals, the hydrolysis rate can be increased by about 0.64%, and both brightness and whiteness are improved. This results in a very small increase in seed crystal cost, simple operation, and stable quality of low-concentration titanium solution hydrolysis.
[0024] 2. By adding a composite treatment agent to the hydrolysis system, on the one hand, the dispersibility of the material in the hydrolysis system can be improved, thereby enabling the seed crystal to induce the titanium liquid to undergo more uniform and complete hydrolysis. On the other hand, the stability of the seed crystal can be enhanced, ensuring the activity of the seed crystal and the nucleation sites, promoting the uniformity of the hydrolysis reaction, thereby improving the hydrolysis rate of the titanium liquid and improving the washing efficiency of hydrolyzed metatitanic acid. Detailed Implementation
[0025] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0026] Example 1
[0027] A process for improving the hydrolysis rate of titanium dioxide produced by the sulfuric acid process includes the following steps:
[0028] S1. Seed preparation: Titanium liquid with a concentration of 250 g / L and an F value of 2.1 and sodium hydroxide solution with a mass concentration of 16% were preheated to 70°C. Then, the titanium liquid was dispersed into the sodium hydroxide solution within 5 min. During the dispersion process, the mixture was stirred at a speed of 350 r / min. The alkali-to-titanium ratio was 0.38. The mixture was then aged at 102°C for 5 min to obtain hydrolyzed seed crystals.
[0029] S2. Hydrolysis: Preheat the hydrolyzed titanium solution with a concentration of 160 g / L and an F value of 1.90 to 98°C. Add 3.5% (by mass of TiO2) of the hydrolyzed titanium solution as hydrolysis seed crystals to form a hydrolysis system. Heat to boiling and maintain a gentle boil. When the hydrolyzed titanium solution turns white, add a composite treatment agent for induction. The mass ratio of the composite treatment agent to TiO2 in the hydrolyzed titanium solution is 0.8%. After induction, continue to heat and maintain a gentle boil for 2 hours. Then add dilution water and maintain a gentle boil for 30 minutes. The hydrolysis is then complete.
[0030] Preparation of composite treatment agent: Mix 5 parts ammonium carbonate, 5 parts aluminum sulfate, and 5 parts potassium sulfate, then add them to 10 parts polyoxyethylene ether phosphate and sonicate for 5 minutes.
[0031] Example 2
[0032] A process for improving the hydrolysis rate of titanium dioxide produced by the sulfuric acid process includes the following steps:
[0033] S1. Seed preparation: Titanium liquid with a concentration of 200 g / L and an F value of 1.95 and sodium hydroxide solution with a mass concentration of 10% were preheated to 80°C. Then, the titanium liquid was dispersed into the sodium hydroxide solution within 6 min. During the dispersion process, the mixture was stirred at a speed of 300 r / min. The alkali-to-titanium ratio was 0.26. The mixture was then aged at 95°C for 20 min to obtain hydrolyzed seed crystals.
[0034] S2. Hydrolysis: Preheat the hydrolyzed titanium solution with a concentration of 180 g / L and an F value of 1.88 to 95°C. Add 5% (by mass) of hydrolyzed seed crystals of TiO2 in the hydrolyzed titanium solution to form a hydrolysis system. Heat to boiling and maintain a gentle boil. When the hydrolyzed titanium solution turns white, add a composite treatment agent for induction. The mass ratio of the composite treatment agent to TiO2 in the hydrolyzed titanium solution is 0.5%. After induction, continue to heat and maintain a gentle boil for 2 hours. Then add dilution water and maintain a gentle boil for 30 minutes. The hydrolysis is then complete.
[0035] Preparation of composite treatment agent: 8 parts ammonium carbonate, 7 parts aluminum sulfate, and 8 parts potassium sulfate were mixed and then added to 15 parts polyoxyethylene ether phosphate, and ultrasonically treated for 8 minutes.
[0036] Example 3
[0037] A process for improving the hydrolysis rate of titanium dioxide produced by the sulfuric acid process includes the following steps:
[0038] S1. Seed preparation: Titanium liquid with a concentration of 160 g / L and an F value of 2.25 and sodium hydroxide solution with a mass concentration of 25% were preheated to 95°C. Then, the titanium liquid was dispersed into the sodium hydroxide solution within 10 min. During the dispersion process, the mixture was stirred at a speed of 350 r / min. The alkali-to-titanium ratio was 0.20. The mixture was then aged at 102°C for 50 min to obtain hydrolyzed seed crystals.
[0039] S2. Hydrolysis: Preheat the hydrolyzed titanium solution with a concentration of 190 g / L and an F value of 1.80 to 98°C. Add 2.5% (by mass of TiO2) of the hydrolyzed titanium solution as hydrolysis seed crystals to form a hydrolysis system. Heat to boiling and maintain a gentle boil. When the hydrolyzed titanium solution turns white, add a composite treatment agent for induction. The mass ratio of the composite treatment agent to TiO2 in the hydrolyzed titanium solution is 1%. After induction, continue to heat and maintain a gentle boil for 2 hours. Then add dilution water and maintain a gentle boil for 30 minutes. The hydrolysis is then complete.
[0040] Preparation of composite treatment agent: 15 parts ammonium carbonate, 10 parts aluminum sulfate, and 10 parts potassium sulfate are mixed and then added to 20 parts polyoxyethylene ether phosphate, and ultrasonically treated for 10 min.
[0041] Experimental Examples 1-5
[0042] The alkali concentration was the same as in Example 1, and the alkali-to-titanium ratios were 0.18, 0.25, 0.31, 0.38, and 0.41, respectively. The remaining treatment processes were the same as in Example 1.
[0043] Table 1 Test Indicators
[0044] Hydrolysis rate % 96.2 96.8 96.7 96.9 96.1 <![CDATA[D 50 / μm]]> 2.736 2.928 2.925 2.930 2.768
[0045] Experimental Examples 8-9
[0046] The alkali-to-titanium ratio was the same as in Example 1, and the alkali concentrations were 10%, 15%, 18%, and 20%, respectively. The remaining treatment process was the same as in Example 1.
[0047] Table 2 Test Indicators
[0048] Hydrolysis rate % 96.1 96.9 96.8 95.8 <![CDATA[D 50 / μm]]> 2.828 3.023 3.014 2.856
[0049] Experimental Examples 10-13
[0050] The alkali concentration and alkali-to-titanium ratio were the same as in Example 1, and the amount of hydrolysis seed crystals added was 2.2%, 3%, 4%, and 10%. The remaining treatment process was the same as in Example 1.
[0051] Table 3 Test Indicators
[0052] Hydrolysis rate % 95.8 97 96.9 95.7 <![CDATA[D 50 / μm]]> 2.996 3.018 3.104 2.916
[0053] Test Example 14
[0054] The difference between this experimental example and Example 1 is that the composite treatment agent does not contain polyoxyethylene ether phosphate.
[0055] Experimental Example 15
[0056] The difference between this experimental example and Example 1 is that the composite treatment agent does not contain ammonium carbonate.
[0057] Experimental Example 16
[0058] The difference between this experimental example and Example 1 is that the composite treatment agent does not contain aluminum sulfate and potassium sulfate.
[0059] Table 4. Experimental Indicators of Examples 1-3 and Test Examples 14-16
[0060] Hydrolysis rate % 97 96.9 96.9 96.1 96.3 96.2 <![CDATA[D 50 / μm]]> 2.931 2.985 3.128 2.715 2.732 2.741 brightness 95.5 95.3 95.1 94.2 94.5 94.6 Whiteness 93.8 93.5 93.5 90.3 91.2 91.5 Black paste b value 0.17 0.19 0.18 0.28 0.31 0.30
[0061] As shown in Tables 1-4, the hydrolysis rate using the process of this invention is higher than 96.5%, the brightness and whiteness are improved, the black paste b value is reduced, and the hydrolysis quality of low-concentration titanium liquid is stabilized.
[0062] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A process for improving the hydrolysis rate of titanium dioxide produced by the sulfuric acid process, characterized in that: Includes the following steps: Seed crystal preparation: Titanium liquid with a concentration of 160-250 g / L and alkaline solution with a mass concentration of 10-25% are preheated separately. Then, the titanium liquid is dispersed in the alkaline solution with an alkaline-to-titanium ratio of 0.20-0.
38. After aging, hydrolyzed seed crystals are obtained. Hydrolysis: Preheat the hydrolyzed titanium solution with a concentration of 160-190 g / L, add 2.5-5% of the TiO2 mass of the hydrolyzed titanium solution as hydrolysis seed crystals to form a hydrolysis system, heat to boiling, maintain a gentle boil, and when the hydrolyzed titanium solution turns white, add a composite treatment agent for induction. After induction, continue to heat and maintain a gentle boil, then add dilution water and maintain the system at a gentle boil. The hydrolysis is then complete. The composite treatment agent comprises, by weight, 5-15 parts ammonium carbonate, 5-10 parts aluminum sulfate, 5-10 parts potassium sulfate and 10-20 parts polyoxyethylene ether phosphate. The mass ratio of the composite treatment agent to TiO2 in the hydrolyzed titanium solution is 0.5-1.0%.
2. The process for improving the hydrolysis rate of titanium dioxide using the sulfuric acid process according to claim 1, characterized in that: The F-value of the titanium liquid prepared by seed crystal preparation is 1.95-2.
25.
3. The process for improving the hydrolysis rate of titanium dioxide using the sulfuric acid process according to claim 1, characterized in that: When preparing seed crystals, the preheating temperature is 70-95℃, the aging temperature is 80-102℃, and the aging time is 5-50min.
4. The process for improving the hydrolysis rate of titanium dioxide using the sulfuric acid process according to claim 1, characterized in that: During seed crystal preparation, the titanium liquid is dispersed into the alkaline solution within 5-10 minutes, and the dispersion is carried out by stirring at a speed of 300-350 r / min.
5. The process for improving the hydrolysis rate of titanium dioxide produced by the sulfuric acid process according to claim 1, characterized in that: The F value of the hydrolyzed titanium solution is 1.80-1.
95.
6. The process for improving the hydrolysis rate of titanium dioxide produced by the sulfuric acid process according to claim 1, characterized in that: The composite treatment agent is prepared by mixing ammonium carbonate, aluminum sulfate and potassium sulfate and then adding them to polyoxyethylene ether phosphate, followed by ultrasonic treatment for 5-10 minutes.
Citation Information
Patent Citations
Method for preparing titanium white by spray hydrolysis
CN101417815A
Method for external seed normal pressure introduced hydrolysis of high-concentration titaniferous solution
CN105883913A